Asprosin Increases Sexual Motivation in Female Rats - Oz, Zeynep Dila; Ozdede, Mehmet Ridvan; Atila, Busra; Horoz, Mert Ali; Yasar, Abdullah; Kacar, Emine; Kelestimur, Haluk (Wiley, 2023)
[Abstract Not Available]
Keywords: Asprosin; Adipokine; Sexual behaviour; Sexual; Motivation